CAN TROIDES HELENA AND PACHLIOPTA ADAMAS CO-EXIST? A PERSPECTIVE FROM THE BUTTERFLY BREEDING FACILITY, CIBINONG SCIENCE CENTER, INDONESIA - Djunijanti Peggie; Supadi Supadi; Guntoro Guntoro; Muhammad Rasyidi (BRIN Publishing (Penerbit BRIN), 2021)
Troides helena and Pachliopta adamas utilize the same food plant species: Aristolochia acuminata. For the purpose of captive breeding and conservation, it is desirable to find out whether they can co-exist in captivity. Captive breeding research was conducted on the butterfly species within the period of October 2016 to September 2019. In total, 1,361 individuals were observed. Data on adult emergence of the species is presented to show population trends. Both species co-existed poorly at the facility when food plants were limited. It took 45.9 days for T. helena helena and 32.6 days for Pc. adamas adamas from egg to imago stage. Habitat enrichment can encourage the species to come and establish the population.